PERANCANGAN MOBILE APPLICATION PADA MATA PELAJARAN KOMPUTER DAN JARINGAN BERBASIS ANDROID - Arita, Arita; Hendriyani, Yeka (INCARE, International Journal of Educational Resources, 2020)
This final project aims to make it easier for users to explore learning materials and stimulate the mindset of users in accessing and receiving information quickly and in real time. This application was created using professional adobeflash with action script 3.0. The results of the interface design are implemented in interactive learning media in the form of Android-based learning applications on Computer and Networking Subjects in class X SMK. Flash projects are stored as * .exe files so that they can be run on a computer or laptop without having to install the adobeflash application and later publish them in a * .apk file so that they can be installed on an Android smartphone. With the application of Digital Simulation learning media for class X based on the android platform, it can help students add insight and sharpen their understanding of class X students regarding Digital Simulation subjects.